MODELING DEMAND FOR TRANSPORT SERVICES IN SUBURBAN - , М. Є. (Municipal economy of cities (Technical science), 2013)
The question of the study factors of the demand for transport services in suburban traffic. The regularities of distribution of the population across depending on the location of settlements relative to the regional center.